Penerapan Model Pembelajaran Terpadu Tipe Nested Untuk Meningkatkan Hasil Belajar Siswa Kelas III Sekolah Dasar (Jurnal Keguruan dan Ilmu Pendidikan, 2021)
This study aims to improve the learning outcomes of third grade students at SDN 3 Sesean, Sesean Subdistrict, North Toraja Regency by using classroom action research with the subjects of the study were all third grade students of SDN 3 Sesean, totaling 30 students consisting of 18 women and 12 men. The techniques and procedures for collecting data in this study consisted of sources of data obtained from test results, teacher and student observation, interviews and documentation using the nested type integrated learning model. This study consisted of two cycles, namely cycle I and cycle II. In each cycle consists of several stages, namely the stages of planning, action, observation, and reflection. The first cycle of the use of the integrated learning model of the nested type conducted by the teacher is adequately qualified (C) with an average value of 50.5, in the second cycle increases because all the steps of learning using nested type integrated learning have been carried out and all indicators are fully implemented so that qualify well (B) with an average value of 71.17. as well as student learning outcomes in each cycle increases from cycle I to cycle II. The conclusion that the researchers obtained in this study was to use the learning model nested in thematic learning with environmental themes can improve learning outcomes of students in class III SDN 3 Sesean Sesean District, North Toraja Regency.